2020
DOI: 10.1002/jrs.5828
|View full text |Cite
|
Sign up to set email alerts
|

Improving Raman spectroscopic identification of rice varieties by feature extraction

Abstract: Raman spectroscopy combined with pattern recognition can identify rice varieties excellently. In this study, a method was established to select the key feature for identification model. Seventy‐two Raman spectra of three varieties of rice were analyzed. Seventy‐one independent variables and characteristic bands (420–560, 820–980, 1,000–1,200, and 1,300–1,500 cm−1) were obtained by principal component analysis (PCA). Window analysis further narrowed the range of characteristic bands (451–550, 951–1,000, and 1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Euclidean distance is one of them. M.Sha et al reported that Euclidean distance gave the best results in their studies based on raman spectroscopy [42]. Looking at Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Euclidean distance is one of them. M.Sha et al reported that Euclidean distance gave the best results in their studies based on raman spectroscopy [42]. Looking at Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Food technologists have not yet reached a consensus on quality classes and measurement methods, so that quantitative indicators and routine metrics for addressing raw-grain quality at the molecular scale are yet conspicuously missing. In this context, Raman spectroscopy offers a unique chance for fast, quantitative, and non-destructive evaluations of rice nutritional value in real time and at low cost [ 5 , 6 ]. Being a “fingerprint” of molecular composition, the Raman spectrum embodies a large amount of structural information.…”
Section: Introductionmentioning
confidence: 99%
“…Sha et al. [ 15 ] distinguished 72 rice varieties using Raman spectroscopy in combination with pattern recognition and reported that protein and starch were the key components that could be used to distinguish the rice varieties at micromolecular level. However, their applications have remained so far very limited for varieties grown under highland Himalayan conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various instrumental techniques can be used to characterize and differentiate starch and other associated components in different varieties of rice. Differential scanning colorimetry (DSC), X-ray diffraction (XRD), and rapid visco analyzer (RVA) can be used to investigate the gelatinization behavior of starches; [13] Fourier transform infrared spectroscopy (FTIR) is a rapid technique, which can be used to identify the functional groups of the molecules; [14] Raman spectroscopy provides information required to elucidate the structure and has better structural selectivity than other spectroscopic techniques, [15] while granular morphology of starch and other associated components can be accessed through scanning electron microscopy (SEM). Shujka et al [14] correlated the content of various nutritional components present in commercial flour samples by both classic chemical methods and FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation